Arabic Digits Recognition by Using Unified Binary Templates in The Digital Images - Sundus Ebraheem (Al-Rafidain Journal of Computer Sciences and Mathematics)
The process of classification and recognition of the digits is very important and accurate issue, it should depend on a strong, adequate rule, because there are differences in the representation of the digits for various type of font,  rather than to get homogeneous classification for group of digits to show the form or the constant shape for the digit from groups of font , where to be one shape represents each group of the shapes and sizes. This paper proposed a new method for recognition images of Arabic digits with various types and size of  font which captured by various kind of camera and various resolution depending on the characteristics of each digit which extracted from study of ten types of font with various size for each type. The characteristic of all shapes and sizes extracted for each digit. Then made a constant model for each digit to be compare with the digit image in any size or font type to recognize the digit in the image. A database of ten templates (one for each digit) built, and these templates are basic and general to recognize the Arabic digits with various font and size. The new method applied for recognition of Arabic digits in the images of license plate of the passenger cars. the recognition percentage was  98%.